(untitled) (Wudil Journal of Science and Technology Education, 2025)
This study investigated the effect of exercise on obese students of the Human Kinetics Department, Aliko Dangote University of Science and Technology, Wudil. The research adopted an experimental design with pre-test and post-test measures. A total of 60 obese students (BMI ≥ 30 kg/m²) were purposively selected and divided into three groups: aerobic exercise group, resistance training group, and control group. Each intervention lasted for eight weeks. Data on body mass index (BMI), cardiovascular endurance, and muscular strength were collected using standardized fitness tests. The data were analyzed using Analysis of Variance (ANOVA). Results revealed significant differences among the groups in BMI reduction (F(2,57) = 8.42, p < 0.05) and cardiovascular endurance improvement (F(2,57) = 10.35, p < 0.01). Post-hoc tests showed that aerobic exercise had the most significant effect on cardiovascular endurance, while resistance training was more effective in improving muscular strength. The study concluded that structured exercise interventions significantly reduce obesity indices and enhance physical fitness profiles. It was recommended that university health programs incorporate structured exercise programs to combat obesity among students.